Investigating developmental changes in sensory processing: visual mismatch response in healthy children - Cleary, Katherine M.; Donkers, Franc C.; Evans, Anna M.; Belger, Aysenil (Frontiers in Human Neuroscience, 2013)
The ability to detect small changes in one’s visual environment is important for effective adaptation to and interaction with a wide variety of external stimuli. Much research has studied the auditory mismatch negativity (MMN), or the brain’s automatic response to rare changes in a series of repetitive auditory stimuli. But recent studies indicate that a visual homologue to this component of the event-related potential (ERP) can also be measured. While most visual mismatch response studies have focused on adult populations, few studies have investigated this response in healthy children, and little is known about the developmental nature of this phenomenon. We recorded EEG data in 22 healthy children (ages 8-12) and 20 healthy adults (ages 18-42). Participants were presented with two types of task irrelevant background images of black and gray gratings while performing a visual target detection task. Spatial frequency of the background gratings was varied with 85% of the gratings being of high spatial frequency (i.e. standard background stimulus) and 15% of the images being of low spatial frequency (i.e. deviant background stimulus). Results in the adult group showed a robust mismatch response to deviant (nontarget) background stimuli at around 150ms post-stimulus at occipital electrode locations. In the children, two negativities around 150ms and 230ms post-stimulus at occipital electrode locations and a positivity around 250ms poststimulus at frontocentral electrode locations were observed. In addition, larger amplitudes of P1 and longer latencies of P1 and N1 to deviant background stimuli were observed in children versus adults. These results suggest that processing of deviant stimuli presented outside the focus of attention in 8-12-year-old children differs from those in adults, and are in agreement with previous research. They also suggest that the visual mismatch response may change across the lifespan in accordance with other components of the visual ERP.